Monkeypox: A comprehensive review of virology, epidemiology, and global health implications - Sheetal Goenka (Microbes and Infectious Diseases, 2025)
Background: Monkeypox, a zoonotic disease caused by the monkeypox virus (MPXV) belongs to the genus Orthopoxvirus within the Poxviridae family. MPXV is a large, enveloped, double-stranded DNA virus with a complex structure typical of poxviruses .It is closely related to variola virus (the causative agent of smallpox), vaccinia virus, and cowpox virus, has emerged as a significant global health concern in recent years. This review provides a comprehensive analysis of MPXV, including its virology, epidemiology, clinical manifestations, diagnostic approaches, treatment options, and prevention strategies. Special emphasis is placed on the current global scenario, highlighting the unprecedented spread of monkeypox beyond its traditional endemic regions. Recent outbreaks have challenged our understanding of MPXV transmission dynamics and underscored the need for enhanced surveillance, rapid diagnostic capabilities, and effective public health interventions. This review article synthesizes the latest research findings and expert opinions to provide an up-to-date perspective on monkeypox, aiming to inform healthcare professionals, researchers, and policymakers in addressing this evolving public health challenge.